IMPLEMENTATION OF PICTURE SEQUENCE TASK TO ASSESS THE NARRATIVE PARAGRAPH WRITING ABILITY OF THE FIRST SEMESTER OF LAW FACULTY - I Gusti Agung Putri Wirastuti; Ida Bagus Nyoman Mantra (Unmas Press, 2019)
The most effective way to improve the students’ writing skill is to first figure out their strengths and weaknesses by assessing their ability through appropriate tasks and scoring procedures. This research was conducted to figure out the more accurate degree of narrative paragraph writing ability of the first semester of Law Faculty which was assessed through picture sequence task. The study made use of ex post facto research with descriptive analysis. Thirty-two of the first semester students of Law Faculty Mahasaraswati Denpasar University were selected by means of random sampling method as samples of the present study. Picture sequence task was used as an instrument to assess their narrative paragraph writing ability. The samples’ works were scored by using analytic scoring rubric which measured format, punctuation and mechanic, content, organization, and grammar and structure. The obtained data were analyzed by using norm-reference measures of standard values. The findings showed that 71.90% of the samples succeeded while the other 28.10% failed. In conclusion, the present study showed that the narrative paragraph ability of the eighth grade students of first semester of Law Faculty Mahasaraswati Denpasar University which was assessed through picture sequence task could be categorized as sufficient.